LATIN IS THE UNIVERSAL LANGUAGE AND ITS BENEFITS OF LEARNING (World Bulletin of Social Sciences, 2025)
The article deals with the phenomenon of Latin as a universal cultural code that continues to be actively used in various spheres of life. Knowledge of Latin not only facilitates the study of many languages, but also allows to attach oneself to the world cultural values, promotes the establishment of links between Latin, ancient culture, and European civilization, gives access to the perception and understanding of works of literature and painting, enhances general erudition and professional competence, expands the cultural horizons.